Davidson, verdad y correspondencia - Caorsi, Carlos (2006)
“Davidson, Truth and Correspondence”. In this paper the A. proposes to analyzeDavidson’s position regarding truth as correspondence, in all of his works.Two periods may herewith be detached: a first one from his first works untilhis 1987 “Afterthoughts”, and a second one, from that date until his last works.What characterizes them is that during his first period Davidson proclaimshimself a correspondist, and in a second period he regrets having adopted thatdenomination, which he characterizes as a terminological error. The A. attemptsto examine which was the reason for that terminological error and how muchof correspondence elements would persist in Davidson later works. For that purpose he proposes to establish a distinction between two  modes o funderstanding correspondence,  related  to two modes of  understandingphilosophical analysis and to what Wright calls the traditional debate concerningtruth, and the new turn the latter should undertake.